2021
DOI: 10.1093/jjco/hyab040
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological atlas of desmoplastic reaction characterization in colorectal cancer

Abstract: Emergent scientific evidence indicates the central role of cancer-associated fibroblasts in determining whether the microenvironment of cancer works as friend or foe of the host; however, there is no unified histological evaluation framework of fibrotic stroma in colorectal cancers. Myxoid stroma and keloid-like collagen are site-specific histopathological features generated by cancer-associated fibroblasts, which appear exclusively in the tumor front during desmoplastic reaction. On the basis of these two str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…First, this study was a retrospective cohort, and selection bias cannot be avoided. Second, some studies have demonstrated that desmoplastic reaction (DR) classification is associated with the prognosis of colorectal cancer 54,55 . However, we cannot clarify the relationship between these four collagen features and the DR category due to the endoscopic forceps being unable to obtain tumor biopsy tissue from the intrinsic muscle layer.…”
Section: Discussionmentioning
confidence: 97%
“…First, this study was a retrospective cohort, and selection bias cannot be avoided. Second, some studies have demonstrated that desmoplastic reaction (DR) classification is associated with the prognosis of colorectal cancer 54,55 . However, we cannot clarify the relationship between these four collagen features and the DR category due to the endoscopic forceps being unable to obtain tumor biopsy tissue from the intrinsic muscle layer.…”
Section: Discussionmentioning
confidence: 97%
“…29 The current study showed that the largest single myxoid stroma area ACP was found to be the most robust prognostic factor, surpassing the significance of both manual DR and automatically detected DR categorised according to the manually determined cutoff value. For manual DR classification via microscopy, the minimum amount of myxoid stroma in immature type is defined as a microscopic field of 409 objective lens, 27 which corresponds to 0.196 mm 2 . Since the area of myxoid stroma within the field of view of a microscope is challenging to assess, this definition is clinically reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…The altered function of CAF induced the transcription of DCN and the leakage into the circulation after degradation, resulting in the attenuation of local DCN and elevation of plasma DCN simultaneously, at least in some patients. Indeed, the expression of stromal DCN was attenuated in the myxoid periductal stromal architecture [ 23 ], produced by CAF [ 24 , 25 ]. Since the stromal expression of DCN exerted protective functions in tumor growth and tumor spreading [ 26 , 27 ], the local delivery of DCN could be a potent novel therapy for inhibiting tumor progression and spreading.…”
Section: Discussionmentioning
confidence: 99%